Enhanced assessment in instrumental programs. - Burrack, Frederick W. (My University, 2011)
Offered in this article are examples of student self and group assessments for use in an instrumental music performance classroom. The purpose is to provide instrumental music teachers an authentic context for applying self and group assessments. Prompted by an intensive, school-wide curriculum project, the instrumental music teachers in Carroll, Iowa expressed concerns relating to the development and documentation of students’ musical understanding,aesthetic sensitivity, and critical listening skills. What developed was a curriculum project in which the instrumental students participated in music portfolio development which included self and group assessments.
Keywords: Music instruction; Student self assessment; Student group assessment; Instrumental music instruction